Riqueza por vivienda de los hogares y sus efectos amplificadores en el consumo (2010)
Considering that housing is the main asset for households, it is relevant to study its behavior and the channel through it affects wealth and consumption. This paper analyzes the effects that changes in housing wealth have on aggregate consumption. In the model considered here, houses work as collateral and households invest in real state. Thus, the model considers a credit constraint and an adjustment cost on investment, in order to analyze their effect on consumption. We conclude that those households with low adjustment cost on investment and using houses as collateral tend to show higher consumption fluctuations due to the accelerator effect